New species of Sinella and Coecobrya (Collembola: Entomobryidae) from New Caledonia - Zhang, Feng; Bedos, Anne; Deharveng, Louis (Zootaxa, 2014)
The genera Sinella and Coecobrya are reported from New Caledonia for the first time, with four new species: Sinella quadriseta sp. nov., S. claviseta sp. nov., S. copiosa sp. nov., and Coecobrya neocaledonica sp. nov. Sinella species studied here exhibit several morphological features that are not found in other non-cave species of the genus: paired teeth on inner edge of unguis closer to the base and distal unpaired tooth very tiny or absent, 2 medio-medial and 1 medio-lateral macrochaetae on Th. II, 2+2 lateral macrochaetae on Abd. III, and abundant short S-chaetae on Abd. IV. The four S-chaetae present on Abd. V are also different from the common pattern in Entomobryidae. C. neocaledonica sp. nov. does not exhibit unique features different from Coecobrya species of other areas.